The influence of arbitrary and pervasive corruption on FDI inflows and the moderating effect of corruption distance: evidence from Latin America - Pessegueiro, Daniel (2018)
There is no consensus in the literature on the negative effect of corruption on countries’ ability to attract foreign direct investment (FDI). Some countries simultaneously have high levels of corruption and FDI flows. In this study, we distinguish the effect of two types of corruption – arbitrary and pervasive – and the moderating role of corruption distance between the investor and host country on the ability to attract FDI. In an empirical study of FDI flows into Latin American countries, the results show that high pervasive corruption reduces the attractiveness of FDI and that corruption distance attenuates the negative effect of arbitrary corruption on FDI. The study contributes to the research on the effects of corruption and particularly to understanding the differentiated effects of the types of corruption and of corruption distance on FDI flows.